Comparative effectiveness of treatment options for displaced midshaft clavicle fractures: a systematic review and network meta-analysis. (16th August 2021) - Martin, John R.; Saunders, Patrick E.; Phillips, Mark; Mitchell, Sean M.; Mckee, Michael D.; Schemitsch, Emil H.; Dehghan, Niloofar
Abstract : Aims: The aims of this network meta-analysis (NMA) were to examine nonunion rates and functional outcomes following various operative and nonoperative treatments for displaced mid-shaft clavicle fractures. Methods: Initial search strategy incorporated MEDLINE, PubMed, Embase, and the Cochrane Library for relevant randomized controlled trials (RCTs). Four treatment arms were created: nonoperative (NO); intramedullary nailing (IMN); reconstruction plating (RP); and compression/pre-contoured plating (CP). A Bayesian NMA was conducted to compare all treatment options for outcomes of nonunion, malunion, and function using the Disabilities of the Arm Shoulder and Hand (DASH) and Constant-Murley Shoulder Outcome scores. Results: In all, 19 RCTs consisting of 1, 783 clavicle fractures were included in the NMA. All surgical options demonstrated a significantly lower odds ratio (OR) of nonunion in comparison to nonoperative management: CP versus NO (OR 0.08; 95% confidence interval (CI) 0.04 to 0.17); IMN versus NO (OR 0.07; 95% CI 0.02 to 0.19); RP versus NO (OR 0.07; 95% CI: 0.01 to 0.24). Compression plating was the only treatment to demonstrate significantly lower DASH scores relative to NO at six weeks (mean difference -10.97; 95% CI -20.69 to 1.47). Conclusion: Surgical fixation demonstrated a lower risk of nonunion compared to nonoperative management. Compression plating resulted in significantly less disability early after surgery compared to nonoperative management. These results demonstrate possible early improved functional outcomes with compression plating compared to nonoperative treatment. Surgical fixation of mid-shaft clavicle fractures with compression plating may result in quicker return to activity by rendering patients less disabled early after surgery. Cite this article: Bone Jt Open  2021;2(8):646–654.